(untitled) - Bartholomew, James R. (New Haven, 1989)
Modern science in Japan has been described as derivative and lacking in creativity. This book argues that Japan has actually built up a tradition of scientific research that is one of the most important in the world by drawing on its own late feudal Tokugawa period and on Western science.
Keywords: Khoa học,Science; Lịch sử,History; Nhật Bản,Japan